Clinical Audit of Psychiatric Discharge Summaries Complying with STOMP (Stopping Over Medication Of People With a Learning Disability and Autism) from Learning Disability Services - Rebecca Fernandes; Claire Donnelly; Padma Babu (BJPsych Open, 2025)
Aims: Long-term administration of psychotropic medications can be associated with significant side effects and physical health problems. There is evidence that people with intellectual disability have overall poorer health than their non-disabled peers. Psychotropic medication prescribed must be reviewed regularly to avoid routine continuation. NICE Challenging behaviour and learning disabilities [NG11] recommends medication should be initiated by a specialist and they should record: